An inquiry on mental health of hospital personnel during pandemic - SHREE, MS K. C. RAJA; SAMNA, MS V. A. (The journal of contemporary issues in business and government, 2020)
The Chinese-born Noval Corona infection disease (COVID-19) It has crossed borders exponentially, infecting individuals around the world.Health care staff face an unparalleled level of emotional pressure associated with COVID19 across technical and personal realms. The goal of this study was to find the impact of mental health on hospital personnel particularly in Andaman and Nicobar Islands government and private medical care frameworks. The examination consisted of 61 participants. Survey questionnaire was provided digitally and manually in person to the respondent. The pervasiveness of stress (37.2%), worry about relatives (41.0%) and isolation (36.1%) were accounted for in the study as an outcome. Protective measures while taking care of patients, checking manifestations, awareness programs, and strategic planning at hospitals should be done. Innovation should be implemented in the healthcare setting to improve the mental health of hospital personnel during pandemic.